Revisão do gênero Umbonia Burmeister (Homoptera, Membracidae, Membracinae, Hoplophorionini) - Creão-Duarte,Antônio J (1996)
Fourteen species of Umbonia are presented with descriptions, illustrations, and a key for Identification. The following nomenclatural changes are introduced: Umbonia articularia Buckton, 1901, sp. reval.; Umbonia pyramidalis Fairmaire, 1846, sp. reval.; Umbonia lativitta Walker, 1851, sp. reval. = U. erecta Goding, 1920, syn.n.; Umbonia crassicornis (Amyot & Serville, 1843) = U. ermanni Griffini, 1895, syn.n. = U octolineata Goding, 1930, syn.n.; Umbonia spinosa (Fabricius, 1775) = U. reducta Walker, 1851, syn.n. = U. terribilis Walker, 1858, syn.n. = U. rectispina Stål, 1869, syn.n. = U. immaculata Funkhouser, 1943, syn.n.. Umbonia struempeli sp.n. (from Brazil); Umbonia formosa sp.n. (from Bolivia) and Umbonia richteri sp.n. (from Colombia).